Fetal lung regeneration using stem cell‐derived extracellular vesicles: A new frontier for pulmonary hypoplasia secondary to congenital diaphragmatic hernia. (3rd March 2022) - Figueira, Rebeca Lopes; Antounians, Lina; Zani‐Ruttenstock, Elke; Khalaj, Kasra; Zani, Augusto
Abstract: The poor outcomes of babies with congenital diaphragmatic hernia (CDH) are directly related to pulmonary hypoplasia, a condition characterized by impaired lung development. Although the pathogenesis of pulmonary hypoplasia is not fully elucidated, there is now evidence that CDH patients have missing or dysregulated microRNAs (miRNAs) that regulate lung development. A prenatal therapy that supplements these missing/dysregulated miRNAs could be a strategy to rescue normal lung development. Extracellular vesicles (EVs), also known as exosomes when of small dimensions, are lipid‐bound nanoparticles that can transfer their heterogeneous cargo (proteins, lipids, small RNAs) to target cells to induce biological responses. Herein, we review all studies that show evidence for stem cell‐derived EVs as a regenerative therapy to rescue normal development in CDH fetal lungs. Particularly, we report studies showing that administration of EVs derived from amniotic fluid stem cells (AFSC‐EVs) to models of pulmonary hypoplasia promotes fetal lung growth and maturation via transfer of miRNAs that are known to regulate lung developmental processes. We also describe that stem cell‐derived EVs exert effects on vascular remodeling, thus possibly preventing postnatal pulmonary hypertension. Finally, we discuss future perspectives and challenges to translate this promising stem cell EV‐based therapy to clinical practice. Key points: What's already known about this topic? The poor outcomes of patients with congenital diaphragmatic hernia (CDH) are directly related to impaired fetal lung development (pulmonary hypoplasia). There is consensus that the prenatal period is a window of opportunity to treat pulmonary hypoplasia and promote normal lung development. Several groups have reported that human and experimental CDH lungs have missing or dysregulated microRNAs (miRNAs). What does this study add? This review collates all the studies that show evidence for stem cell derived‐extracellular vesicles (EVs) as a therapy to rescue normal development in CDH fetal lungs. EVs administered to models of pulmonary hypoplasia transfer cargo, including miRNAs that are in part responsible for the EV regenerative effects.